Application of the Guided Inquiry Model to Improve Science Process Skills High School Students - Ade Rahayu Fadhilla; Muhibbuddin Muhibbuddin; Muhammad Syukri (Postgraduate, University of Mataram, 2021)
This study aims to improve students' science process skills by applying a guided inquiry learning model to the concept of work and energy learning physics. The research design used was a quasi-experimental control group design. The population in this study was all class X MIA SMA Negeri 5 Banda Aceh, which consisted of five parallel classes who took the science program in the even semester of 2020/2021 with a total of 139 students. Two classes as the research sample were selected by purposive sampling by taking into account the average value of physics for each class. Meanwhile, the determination of the experimental and control classes in this study was carried out randomly. Data on science process skills in both classes was obtained through observation sheets filled out by two observer teachers. The results of data analysis show that, in general, there is a significant difference between the improvement of science process skills in the experimental class and the control class for the indicators of observing, predicting, measuring, communicating, and concluding. However, for classifying indicators, the results were not significantly different. The improvement of science process skills in the experimental class in general for all of these indicators certainly cannot be separated from each step of the guided inquiry learning model they carry out. The positive results of the implementation of physical learning through the inquiry model on students' science process skills can be used as a reference and support for teacher implementation in carrying out the teaching and learning process of physics, especially on the concept of business and energy